Solid state spectroscopies basic principles and applications - Gonzalo, Julio A. (World Scientific Pub. Co., 2002)
Materials physics is a very active research field at present and it is expected to remain so in the foreseeable future. Different spectroscopies are currently used to investigate the structure and dynamics of crystalline materials. Some traditional spectroscopies are presented in this book: optical, magnetic resonance, ultrasonic, brillouin, neutron scattering, soft mode and dielectric response spectroscopies. For all of them, the presentation is complemented with some reference material for more modern or sophisticated spectroscopies. This book should be useful as an introductory textbook for a short course on solid state spectroscopies. A number of exercises are worked out throughout the text. Ferro- and piezoelectric materials and their phase transitions are paid special attention